Legal problems of implementation of international social obligations by the Republic of Kazakhstan - Mezhibovskaya И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
The article provides a scientific and practical analysis of some of the international obligations of the Republic of Kazakhstan in the social and labor sphere, presented in interstate agreements ratified by Kazakhstan. At the same time, most of the international documents studied in the article are concluded within the framework of the CIS and the EAEU. The main scientific emphasis is placed on legal incidents that are fixed in contractual texts, initially condemning international obligations to the impossibility of their fulfillment, as well as on interstate obligations, the functioning of which has now lost its relevance and expediency and, therefore, are not actually performed, but at the same time preserving the legal force of priority over the laws of the Republic of Kazakhstan. Non-fulfillment or improper fulfillment of international obligations from the point of view of the country’s Constitution and international standards is unacceptable. However, such problems are now fixed in the field of pension provision, including issues of pension assignment and their payment, benefits in social benefits, medical care and social insurance, labor, employment, etc. Significant problems in the framework of international regulation and cooperation are often caused by serious differences in national legislative systems, different visions of state tasks and priorities, the lack of full-fledged scientific legal expertise in terms of unification of different national legal systems, and sometimes high-quality long-term actuarial forecasts. The article offers options for the legal resolution of some problems regarding the implementation of Kazakhstan’s international obligations.